Cfd Study of Cavern Ventilation - Hurtado-Cruz, J; Carvajal-Meza, M (CRC Press/Balkema, 2023)
The ventilation of mines and underground works has been studied for more than 100 years, with extensive and rigorous results that currently aid in safely performing underground operations of different kinds and characteristics. However, the study of underground ventilation in large volumes such as caverns has seen relatively little open study, being part of engineering studies without further disclosure. In general terms, it is the final use of the cavern that determines the ventilation system to be used. In this regard, the present study is generated from the need to define elementary ventilation systems for underground caverns linked to the construction system, which allows for maximum pollutant drag with minimum flow rate and reducing recirculating secondary flows. For this, Computational Fluid Mechanics is used as a simulation and analysis tool through the Ansys Fluent software, generating various simulation scenarios of steady and transient flows. The results show different ways of ventilating according to the established boundary conditions and the construction geometries used, which could help to orientate future ventilation designs from an academic exercise. © 2023 The Author(s).